2018
DOI: 10.14710/hnhs.1.1.2018.24-34
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mindfulness on the Decreasing Anxiety in Nursing Students to Support Academic Learning: A Literature Review

Abstract: Background: Anxiety and stress in nursing students has been shown to result in a lack of concentration, reduced learning productivity, and unfavorable physiological effects. This can cause a bad risk to the academic process of nursing students. A positive coping mechanism to reduce anxiety can be performed through various mindfulness training to support the academic success of nursing students.Purpose: This literature review study aimed to describe the influence of mindfulness on decreasing anxiety in nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…For example, they can drink medication as prescribed; enough rest; and find time to laugh: Self-preparation with factual information related to the viruses, and take preventive actions and other ways that needed to adapt to the condition changes; limit or increase the new exposure, according to preference; food sustainability; plan the daily activity; and anticipate potential short-term stress, seeing friends, and loved one. Writing daily notes every day including the event, goal, and meaning of life from any difficulties proved to be helpful because a study showed that the expressive writing and expression of emotional experience will be a benefit for psychological and physical [18], [25]. Coherence was conducted through the mindfulness practice while connectedness was conducted through loving-kindness meditation [18], [23], [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, they can drink medication as prescribed; enough rest; and find time to laugh: Self-preparation with factual information related to the viruses, and take preventive actions and other ways that needed to adapt to the condition changes; limit or increase the new exposure, according to preference; food sustainability; plan the daily activity; and anticipate potential short-term stress, seeing friends, and loved one. Writing daily notes every day including the event, goal, and meaning of life from any difficulties proved to be helpful because a study showed that the expressive writing and expression of emotional experience will be a benefit for psychological and physical [18], [25]. Coherence was conducted through the mindfulness practice while connectedness was conducted through loving-kindness meditation [18], [23], [25].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-three from 40 and 25 from 34 studies showed a significant decrease in anxiety and stress for each; 22 from 24 studies should improve in attention [22], [24]. Overall, ME promised in decreasing stress and anxiety for students [25].…”
Section: Introductionmentioning
confidence: 91%
“…Fenomena depresi merupakan salah satu kejadian yang banyak terjadi pada mahasiswa dan memerlukan penanganan dini dari pengalaman yang mungkin dihadapi mahasiswa. Studi literatur tentang masalah psikologis baik pada remaja maupun khususnya dikalangan mahasiswa juga cenderung tinggi, dan jumlah mahasiswa yang mengalami depresi yang disebabkan karena faktor akademik meningkat setiap tahunnya (Wiguna, Dwidiyanti, & Sari, 2018).…”
Section: Pendahuluanunclassified
“…Until now, studies on anxiety in education have shown a negative relationship with respect to academic performance [20], content assimilation [21] and metacognitive processes [22]. In contrast, anxiety, in an academic context, has been positively related to stress [23], frustration [24] and emotional distress [25].…”
Section: Mathematical Anxietymentioning
confidence: 99%